Enhancing Accessibility and Inclusivity of Digital-Based Hajj-Umrah Services for Muhammadiyah KBIHU Hajj-Umrah Guides in Semarang City - Sriyono; Mohammad Ridwan; Sukamto; Danusiri; Ilham Bayu Pamuji (Edumedia Solution, 2026)
This community service program aims to enhance the competencies of Hajj–Umrah instructors through the utilization of digital service solutions that improve accessibility and effectiveness of guidance. The program was implemented using the Kurt Lewin Classroom Action Research (CAR) model, consisting of planning, action, observation, and reflection stages, and involved 125 instructors and participants from KBIHU Muhammadiyah Kota Semarang. The evaluation results indicate consistent improvement in participants’ abilities. Initial observations showed a comprehension level of 56%, which increased to 76% after the first action using conventional learning. In the final post-test following digital service–based instruction, participants’ understanding further improved to 86%. These findings demonstrate that digital service effectively strengthens learning through more accessible and interactive material delivery. Overall, the program confirms that integrating digital technology into Hajj–Umrah guidance enhances instructor competence and supports KBIHU’s transformation toward more adaptive and inclusive service delivery.